2023
DOI: 10.1186/s12964-023-01348-1
|View full text |Cite
|
Sign up to set email alerts
|

IL-1β mediates the induction of immune checkpoint regulators IDO1 and PD-L1 in lung adenocarcinoma cells

Afshan Fathima Nawas,
Ashley Solmonson,
Boning Gao
et al.

Abstract: Introduction Inflammation plays a significant role in various cancers, including lung cancer, where the inflammatory cytokine IL-1β is often elevated in the tumor microenvironment. Patients with lung adenocarcinoma show higher levels of serum IL-1β compared to healthy individual. Moreover, IL-1β blockade reduces the incidence and mortality of lung cancer. Our prior studies revealed that alveolar type-II cells, the precursors for lung adenocarcinoma, display an induction in the expression of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Garcia-Diaz et al [ 111 ] demonstrated that the STAT1/3 signaling targeted the interferon regulatory factor 1 (IRF1) which subsequently transactivated the promoter of the PD-L1 gene in human melanoma cells. Not only cytokines, such as IL-1β, IL-17, TNF-α, and GM-CSF, but also reactive oxygen species (ROS), UV irradiation, and lipopolysaccharide triggered the expression of PD-L1 via NF-κB signaling under many experimental conditions [ 114 119 ]. Recently, Lu et al [ 120 ] revealed that the NLRP3 inflammasome, which is primed by NF-κB signaling, upregulated the expression of PD-L1 in mouse lymphoma.…”
Section: The Aging-associated Signaling Stimulates the Expression Of ...mentioning
confidence: 99%
“…Garcia-Diaz et al [ 111 ] demonstrated that the STAT1/3 signaling targeted the interferon regulatory factor 1 (IRF1) which subsequently transactivated the promoter of the PD-L1 gene in human melanoma cells. Not only cytokines, such as IL-1β, IL-17, TNF-α, and GM-CSF, but also reactive oxygen species (ROS), UV irradiation, and lipopolysaccharide triggered the expression of PD-L1 via NF-κB signaling under many experimental conditions [ 114 119 ]. Recently, Lu et al [ 120 ] revealed that the NLRP3 inflammasome, which is primed by NF-κB signaling, upregulated the expression of PD-L1 in mouse lymphoma.…”
Section: The Aging-associated Signaling Stimulates the Expression Of ...mentioning
confidence: 99%